Prediction of molecular properties and molecular spectroscopy with density functional theory: From fundamental theory to exchange-coupling - Neese, Frank (Coordination chemistry reviews, 2009)
This review provides a detailed account of density functional theory (DFT) and its application to the calculation of molecular properties of inorganic compounds. After introducing some fundamental quantum mechanical concepts, the foundations of DFT and their realization in the framework of the Kohn–Sham construction are described. Following a brief exposition of the computational machinery required to carry out large-scale DFT calculations, the application of analytic derivative theory to DFT is developed in some detail. The cases covered include geometric, electric, magnetic and time-dependent perturbations. The developed theoretical apparatus is then applied to the calculations of molecular structures, vibrational energies as well as a wide variety of properties including absorption, circular dichroism, magnetic circular dichroism, resonance Raman, X-ray absorption, Mössbauer and electron paramagnetic resonance spectroscopies. Finally, the important subjects of spin state energetics and exchange couplings in oligomeric transition metal clusters is discussed.